SUMBANGAN KOSA KATA BAHASA SANSEKERTA TERHADAP PERKEMBANGAN BAHASA INDONESIA DAN JAWA BARU - -, Hardiyanto; Widayat, Afendy (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2006)
In their development, the languages referred to as Bahasa Indonesia (orBI, for short) and New Javanese (or NJ, for short) have absorbed a quantity oflexicon from Sanskrit. Much of the same lexicon has been absorbed from Sanskritinto BI and NJ. Granted that BI and NJ influence each other, perhaps BI hasabsorbed the Sanskrit lexicon from NJ or vice versa. However, referring tohistorical aspects, it is highly likely that the two have had access to Sanskrit froman old or ancient version of Javanese because Sanskrit has no longer been a livinglanguage since the 10th century.The process of the absorption of the Sanskrit lexicon into BI and NJ isdivisible into at least three types: (1) without phonological, morphological, andsemantic changes, (2) with phonological and semantic changes but withoutmorphological changes, (3) with phonological changes but without morphologicaland semantic changes, The last-mentioned type is further divisible into at least fivesub-types: (1) with a consonant shift, (2) with a long vowel changed into a shortone, (3) with a double consonant changed into a single one, (4) with a phonologicaladdition, and (5) with a phonological elimination.Keywords: Sanskrit, Bahasa Indonesia, Javanese, lexical contribution